Maternal role and psychosocial development of children aged 36-59 months - Erni Samutri; Ika Rahmawati; Wahyuningsih Wahyuningsih; Anafrin Yugistyowati; Yhona Paratmanitya (Alma Ata University Press, 2023)
Background : Each child will probably achieve each early developmental aspects at different times. The achievement of child development is determined by various inputs, including child input, maternal input, family input, and environmental input. However, failure to fulfill these inputs has an impact on development delay, especially psychosocial development aspect. Parents, especially mothers, have a significant role in providing these inputs Objectives: To identify the relationship between maternal input including sociodemographic characteristics and the maternal role and the psychosocial development of children aged 36-59 months.Methods: This study was a cross-sectional conducted in February 2020 in Puskesmas Sedayu 2, Yogyakarta. The eligible participant was mothers of children aged 36-59 months. The questionnaires included sociodemographic data, parent role questionnaires, and psychosocial development questionnaires. The correlation between variables was analyzed using a Spearman rank test.Results: This study included 89 mothers with children aged 36-59 months. About 91% of children were in normal psychosocial development. Correlation on sociodemographic characteristics showed that the mother's occupation was significantly related to the psychosocial development of children aged 36-59 months (p=0.005). Maternal role also show significant correlation with children psychosocial development (p=0.007). In addition, there were 2 domains of the maternal role that showed significant relationship with child psychosocial development, namely the role as a caregiver (p= 0.002) and counselor (p=0003).Conclusions : The achievement of psychosocial development of children aged 36-59 months is related to the mother's occupation and the mother's role. Fulfilling each dimension of the parent's role will optimize all aspects of child development, including psychosocial aspects in preschool children to become children who have a positive self-concept, be creative, dare to show initiative.